Parental Attitudes and Motivation to Save Energy in the Perception of Young People with ASD. Implications for Energy Education and Financial Education - Anna Gagat Matuła; Frączek Bożena; Katarzyna Plutecka (Communications of International Proceedings, 2021)
The aim of the research is to try to answer the question: Are parenting attitudes of mothers and fathers, and if so which ones, related to the motivation to save energy in the perception of young people with ASD? Many studies have confirmed and provided a deeper understanding of the specificities of motivation deficits in autism and their relationship to the acquisition of many skills and to later behavior - also to energy saving behavior. The research found that the best results in motivating children with ASD to adopt energy saving behavior were achieved by accepting, supporting and loving parents (of the father in acceptance and the autonomous parental style). Enhancing the motivational system, including prosocial e.g. energy saving behavior in children with ASD, is a great challenge for both parents as well as the educational system.
Keywords: Energy Savings; Motivation; Parental Attitudes; Youth With ASD